2014
DOI: 10.1186/1939-4551-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology approaches to understanding Epithelial Mesenchymal Transition (EMT) in mucosal remodeling and signaling in asthma

Abstract: A pathological hallmark of asthma is chronic injury and repair, producing dysfunction of the epithelial barrier function. In this setting, increased oxidative stress, growth factor- and cytokine stimulation, together with extracellular matrix contact produces transcriptional reprogramming of the epithelial cell. This process results in epithelial-mesenchymal transition (EMT), a cellular state associated with loss of epithelial polarity, expression of mesenchymal markers, enhanced mobility and extracellular mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 117 publications
4
102
0
Order By: Relevance
“…Studies of systems and integrative biology address exactly these challenges, and are now emerging as critical in advancing all branches of biomedical science. Next generation sequencing technology, shared availability of “big data” and advances in computational biology are new promising tools for discovery of novel drivers of barrier dysfunction 150, 151 .…”
Section: Identifying Key Drivers Of Defects and The Basis For Prementioning
confidence: 99%
“…Studies of systems and integrative biology address exactly these challenges, and are now emerging as critical in advancing all branches of biomedical science. Next generation sequencing technology, shared availability of “big data” and advances in computational biology are new promising tools for discovery of novel drivers of barrier dysfunction 150, 151 .…”
Section: Identifying Key Drivers Of Defects and The Basis For Prementioning
confidence: 99%
“…We discovered modules enriched in action modes that point to how different processes modulating the activity of NF-jB/RelA. We generated an EMT contextspecific modulatory subnetwork comprising extracellular matrix formation, actin polymerization pathways, and long intergenic non-protein-coding RNA regulated by EMT (Ijaz et al, 2014). This information may provide potential drug targets for EMT-related cancer progression.…”
mentioning
confidence: 99%
“…Maintenance of epithelial integrity is critical to normal cellular signaling, pulmonary homeostasis, and response to toxicants and allergen exposures. Moreover, this cell type plays a dynamic role in initiating innate signaling programs in response to physical, chemical and biological challenge through coordinating secretion of cytokines, defensins, and alarmins [2;3]. Injury, subsequent inflammation and the loss of epithelial basement membrane integrity also promote epithelial cell activation by extracellular matrix-associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have found that EMT also produces complex alterations in the tumor necrosis factor (TNF)α, signal transduction pathway [10]. The EMT state produces profound changes in TNFα signaling pathway coupling its canonical and noncanonical arms through transcriptional reprogramming of the TRAF1 and NFκB1 promoters [3;10]. As a result, the “coupling constant” e.g., the lag time between activation of the canonical and the noncanonical NF-κB program, was markedly reduced by EMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation